РЕДУКЦИЈА УРБАНИХ ТОПЛОТНИХ ОСТРВА И ПОБОЉШАЊЕ ТОПЛОТНОГ КОМФОРА СТАНОВНИКА - РЕШЕЊЕ ЗАСНОВАНО НА ПРИРОДИ: - Đorđević, Tomislav (Arhitektura i urbanizam, 2021)
The benefits of urban blue-green  infrastructures are well known: they intercept airborne three-atom particles, thus reducing pollution levels; and they provide shade and cooling by means of evapotranspiration. The focus of this paper is to demonstrate methods such as remote sensing and multi-spectral analysis, which can be a very useful addition to the quantification of blue-green  infrastructures for cooling and shading, especially in the  highly  complex geometry of city blocks. The basic aim of this research is to attempt to reduce urban heat islands and in this way to indirectly increase the comfort of living. A cause/effect relationship between the envelope of built up structures and the solar radiation distribution on the environment was established by means of mulit-spectral analysis, and an estimation was made concerning the lack of vegetation on a specific parcel/block (an important tool for urban planners).This state-of-the-art methodology was applied to the optimized prediction concept of vegetation resources. Now it is possible to create a model that will incorporate this newly-added urban vegetation into urban plans, depending on the evaporation potential that will affect the microclimate of the urban area. Such natural cooling can be measured and adapted and hence aimed at a potential decrease in temperature in areas with UHI emissions.As a case study, part of  a seacoast urban block (Abu Dhabi UE,)  was  analysed with and without a street treeline and green façades and roofs. It was concluded that green infrastructure reduced the land surface temperature by up to 4.5˚C.
Keywords: урбана топлотна острва (UHI); температура површине земљишта (LST); намена земљишта (LULC); оптимални количник вегетативног индекса (NDVI)